2022-RA-459-ESGO UPLIFT (ENGOT-ov67/GOG-3048) a registrational trial of Upifitamab Rilsodotin (XMT-1536; UpRi), a NaPi2b-directed antibody drug conjugate (ADC) in platinum-resistant ovarian cancer. (20th October 2022) - Concin, Nicole; Monk, Bradley J; Mirza, Mansoor Raza; Coleman, Robert L; Ray-Coquard, Isabelle; Pothuri, Bhavana; Baurain, Jean-Francois; Alejandro Perez-Fidalgo, J; Cibula, David; Saverse, Antonella; Banerjee, Susana; Madry, Radek; et al.
Abstract : Introduction/Background: UpRi is a first-in-class NaPi2b-targeting ADC with a novel scaffold-linker-payload that enables high drug-to-antibody ratio and controlled bystander effect. NaPi2b is a sodium-dependent phosphate transporter protein broadly expressed in high-grade serous epithelial ovarian, fallopian tube and primary peritoneal cancers (HGSOC), with limited expression in healthy tissues. Preliminary antitumor activity from the Phase 1b expansion cohort of heavily pretreated patients with recurrent HGSOC has been reported (Richardson et al., SGO 2022). These data suggested clinically meaningful activity in patients, notably in those with NaPi2b-high tumors (TPS≥75). Effective and well-tolerated treatments for platinum-resistant ovarian cancer (PROC) remain a substantial unmet medical need. The standard of care, single agent chemotherapy, has limited efficacy, significant toxicities, and short duration of response. UPLIFT was designed as a single-arm Ph2 registrational trial for UpRi monotherapy in PROC. Methodology: UPLIFT is enrolling patients with platinum-resistant HGSOC with up to 4 prior lines of therapy (LoT). Prior bevacizumab is required for patients with 1–2 prior LoT only; it is not required for patients with 3–4 prior LoT. Patients may enroll regardless of NaPi2b expression; ≤ Grade 2 peripheral neuropathy is permitted. Primary platinum refractory patients are excluded. UPLIFT will enroll ~180 patients globally, including approximately 100 patients with NaPi2b-high expression. UpRi will be dosed intravenously at 36 mg/m 2 up to ~80 mg dose maximum every 4 weeks. Baseline tumor samples (fresh or archived) will be collected for central analysis of NaPi2b expression. Based on data from the Ph1b expansion cohort, the cut-off for high NaPi2b expression is Tumor Proportion Score (TPS) ≥75. The primary endpoint is ORR in NaPi2b-high expressing patients. Secondary endpoints include ORR in the overall population, duration of response, and safety. UPLIFT is being conducted in collaboration with ENGOT (ENGOT-ov67) and GOG (GOG-3048). NCT03319628 Results: N/A trial in progress Conclusion: N/A trial in progress